Morphological characterization and hierarchical classification of 40 bush pea genotypes (Pisum sativum L.) - Rosero-Lombana, Verónica; Checa-Coral, Oscar (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The Universidad de Nariño is home to a collection of bush pea plantlets that are a source of biodiversity for the genetic improvement of pea species in Colombia. The characterization of these accessions is required to identify genotypes with attributes that could be used in the search for new varieties. For the morphological characterization, 40 pea accessions were planted in Pasto, Colombia. 23 quantitative variables and 12 qualitative variables were documented, descriptors proposed for this species by the European Union in 2003. The data were subjected to Principal Component Analysis and Multiple Correspondence Analysis. Finally, a hierarchical classification method was applied using Ward’s method. The first four components, which explained 78.80% of the total variability of the population, were selected for the quantitative variables. Four groups were identified. Genotypes with the afila gene, which are of interest for pea breeding programs, were found in groups 1 and 2. The highest seed weight was in group 1, and the genotypes with the best reaction to powdery mildew were in group four. For the qualitative variables, the first six factors, which described 60.51% of the variability, were selected, and the hierarchical classification analysis resulted in five groups. The qualitative characteristics that contributed more to the differentiation of the groups included leaflet type, hilum color, degree of curvature of the pod, color and shape of the grain.